Potential for Development and Limitations of Regional Business Environment - Solodilova, Natalia Zinovyevna; Malikov, Rustam Ilkamovich; Grishin, Konstantin Evgenevich (Economy of Regions, 2015)
The article deals with the institutional support of the regional business environment. Due to the constant growth of social obligations of the regional and municipal authorities causing the growth of the risks of imbalances in the budgets of the respective levels, the necessity of development in the regions of favorable business environment conducive to enhancing business activity is proved. Using the methodology of the institutional matrix business model, the process of development of the institutions of the business environment in the region is analyzed. The mechanism influencing the occurrence of the specific characteristics of the institutional configuration of the regional business environment is revealed. The conclusion of the determining role of the institutional configuration of the business environment in the existing differences in the levels of socio-economic development of regions is drawn. The hypothesis is made that the maintenance of a favorable institutional configuration of the regional business environment stimulating business activity in a territory cannot be indefinitely, and its development is cyclical. The modeling of parameters of development and maintains a favorable institutional configuration of the business environment in the Russian regions is made. For the purposes of the practical application of the proposed approach, the methodological tools, which allows regional authorities to calculate the profitability of a favorable institutional configuration of the business environment and on the basis to form the business rules ensuring the growth of business activity and increase the contribution of business to socio-economic development of the region are proposed. The approach considered in the article provides an opportunity to validate the theoretical - methodological basis for the development of practical design mechanism and maintenance of a favorable long-term future of the institutional configuration of the business environment promoting the growth of business activity in a region resistant to the adverse effects of the environment.